Implementation of Solid Water and Waste Water Management of Beach Resorts in Anda, Bohol, Philippines - Jesszon Cano; Arlinda Ramasola; May Amor Gucor; Lilanie Olaso; Darwin Lim; Kingie Micabalo (Philippine Association of Institutions for Research, Inc., 2021)
Resorts operation in developing economies has provided a visible contribution towards improving the economy through tourists' spending and countless social transformation. However, in any economic growth, environmental integrity has always been compromised by its future viability. This study aims to determine the extent of the implementation of solid waste and wastewater management and the contribution of the beach resort. The findings of this study served as a basis for devising an environment-friendly model for beach resorts. This investigation utilized the descriptive-correlational method of research with the use of researcher-designed survey tools. This study was conducted in Anda, Bohol. Using the purposive sampling technique, twenty respondents provided information on their demographic profile and the extent of solid waste and wastewater management implementation in the beach resorts. Frequency count and percentage, weighted mean, chi-square test of independence were computed. More respondents belonged to the 40 & above age range, and the majority were females, single, college graduates, and worked as general managers of the beach resorts. The solid waste management of waste minimization and waste reuse was moderately implemented, while wastewater management was highly implemented.